Optimized CNN Model for Diabetic Retinopathy Detection and Classification - Maithili, K.; Latha, Y. Madhavi; Gangopadhyay, Amit; Varghese, Issac K.; Sundaram, Ajith; Pandey, Chetan; Kiran, Ajmeera (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Nowadays, retinopathy detection and classification is considered as most effective identification approach for many diseases. Moreover, Detection of veins in the retina is a significant perspective in the discovery of disease and is done by isolating the retinal veins concerning the fundus retinal images. Likewise, it yields the irreplaceable realities about the retina expected for the recognition of infections because of expanded glucose levels and pulse levels, which give prior distinguishing proof in retinal vessels. This assists with giving prior treatment to lethal illnesses and forestalls further effects because of diabetes and hypertension. In this paper, an innovative hybrid Strawberry-based Convolution Neural Framework (SbCNF) is designed to detect and classify the retinopathy disease from the retinal images. Different datasets are utilized to section theretinal veins. Here, DRIVE datasets are used as the entire execution. The execution of this research is done on the python platform. Moreover, this study provides the potential improvement in the retinopathy detection application. The implementation outcomes have been validated with the traditional classification models methods in terms of accuracy, precision, recall, F-measure, etc. The analysis demonstrates that the designed algorithm achieved the finest accuracy in retinopathy recognition due to its effective advantages like less computational complexity.